DETERMINANTS AND OPTIMAL LEVEL OF CORPORATE CASH HOLDINGS: EVIDENCE FROM US, UK AND JAPAN - Zhang, Shan Shan (2013)
This paper firstly investigates the empirical determinants of corporate cash holdings for a sample of listed US, UK and Japanese firms during the 2000-2012 period. Through applying the pooled time-series cross-sectional estimations, cross-sectional estimations and GMM two-step method of estimations, the results reveal that firms’ cash flow, cash flow variability, bank debt and degree of shareholders protection and creditor protection all have inverse relationship with cash holdings. Contrarily, research and development expenses, taxes, days to collect accounts receivables and current ratios exert positive effects on cash reserves. The results of determinants support the Trade-off theory except for cash flow variability. Besides, the significant non-monotonic relationship has been identified for growth opportunities, leverage and liquid asset substitutes. However, firm size and dividend are tested to be insignificance to determine cash holdings in our sample. This paper also verifies the firms’ mean reverting and target adjustment behaviours. Subsequently, the existence of optimal amount of cash holdings could be proved and the approximate optimal amounts are estimated for the samples of US, UK and overall.